2011
DOI: 10.1038/jhh.2011.71
|View full text |Cite
|
Sign up to set email alerts
|

Associations of serum salusin-alpha levels with atherosclerosis and left ventricular diastolic dysfunction in essential hypertension

Abstract: Serum salusin-alpha, is decreased in essential hypertension and acute coronary syndrome. The study is aimed to explore whether serum salusin-alpha is associated with atherosclerosis and left ventricular (LV) diastolic dysfunction in essential hypertension. Echocardiography, carotid ultrasonography, brachial-ankle pulse wave velocity (BaPWV) and serum salusin-alpha levels were determined in 60 hypertensive patients (29 with and 31 without carotid plaque) and 30 normotensive controls. Hypertensive patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 27 publications
1
22
1
Order By: Relevance
“…Our data and others have demonstrated that decreased levels of serum salusin- α are associated with carotid atherosclerosis and cardiac dysfunction in patients with essential hypertension and with renal dysfunction in patients with chronic kidney diseases [4547]. We recently suggested the possible mechanisms responsible for decreased production of salusin- α in atherosclerotic lesions.…”
Section: Linkage Of Salusins With Atherosclerotic Cardiovascular supporting
confidence: 54%
“…Our data and others have demonstrated that decreased levels of serum salusin- α are associated with carotid atherosclerosis and cardiac dysfunction in patients with essential hypertension and with renal dysfunction in patients with chronic kidney diseases [4547]. We recently suggested the possible mechanisms responsible for decreased production of salusin- α in atherosclerotic lesions.…”
Section: Linkage Of Salusins With Atherosclerotic Cardiovascular supporting
confidence: 54%
“…Therefore, elevated peripheral salusin-β levels could represent the amount of peptide secreted by macrophages in response to vascular inflammatory processes. Recent studies have reported that serum salusin-α levels, which possess contrasting antiatherosclerotic activity by suppressing macrophage foam cell formation, are lower in patients with coronary artery disease, hypertension, and renal failure than in healthy controls, and the magnitude of decrease in serum salusin-α appears pronounced as atherosclerosis advances [7,15,17,21]. Therefore, salusin-α has been proposed as a candidate biomarker for atherosclerotic and cardiovascular diseases in humans [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, compared with healthy volunteers, patients with coronary artery diseases manifest reduced concentrations of serum salusin-α [6]. Serum salusin-α level is also associated with atherosclerosis and left ventricular diastolic dysfunction in essential hypertension [7], [8]. In addition, our recent study shows that the expression of salusin-β is increased in the vascular tissues of low-density lipoprotein receptor-deficient (LDLR-/-) mice fed on high-fat diets compared with that of C57BL/6 control mice [9].…”
Section: Introductionmentioning
confidence: 99%